Implementasi Animasi Pada Multimedia Interaktif - Chang, Michael; Liliana, Liliana; Rostianingsih, Silvia (Jurnal Infra, 2015)
Most  people  do  reading  activities  to  gain knowledge,  as entertainment or a hobby for people to read. From generation to generation,  reading  begins  to  decreases.  Reading  becomes obsolete. Nowadays, reading a book filled with writing would be boring.  Books  preferably  instant  and  interesting  than  a  book filled with long writing and tedious. While in general almost all history  books  are  full  of  writing.  So  this  time  i  will  make  an interactive multimedia that interesting and not boring about the history of the kingdom of Majapahit.In the manufacture of interactive multimedia about the history of Majapahit  i  implemented  several  important  elements  in interactive  multimedia  ie  text,  images,  sounds,  and  animations are  placed  and  adjusted  the  alignment  between  text,  images, sound, and animation. The  menu also made efficiently so that it can move from one topic to another topic. The addition of some visual effects that make interactive multimedia applications about the history of Majapahit becoming more.The apllication was tested to some people to see  if the interactive multimedia  about  the  history  of Majapahit  interesting  or  not. Amounting to 75,52% people said that the interactive multimedia about the history of Majapahit is more interesting rather than the book full of writing.